‘Watch and do what I do’: ethnographic fieldnotes from the online salsa class - Ana, Ruxandra (Taylor & Francis, 2022)
Restrictions on movement and requirements for social distancing during the COVID-19 pandemic have triggered an almost total shift to digital creation, teaching, and promotion in the field of dance. By employing an (auto)ethnographic lens, this article explores collective and individual embodied knowledge acquired through online dance classes, with a particular focus on Cuban social dance genres. Music and dance were core components of the Cuban tourism industry, an important pillar of the Cuban economy which was brought to a halt by the pandemic. Dancers’ participation in the global dance market through transition to online dancing was hindered by the struggles of everyday life in Cuba, yet their resilience and resourcefulness allowed them to transform their previous routines and pedagogies following the same mechanisms that lead to the emergence of a Cuban dance market in the first place. The article reflects upon the disruptions of old dynamics and emergence of new ones, by focusing on shifting methodologies of Cuban dance, strategies for monetizing creative labour, and the female dancing body as transformative space.
Keywords: salsa; dance; online teaching; Cuba; dance pedagogies; dance labor